2020
DOI: 10.1111/apa.15186
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review presenting a wide variety of research on paediatric and adolescent patients with Marfan syndrome

Abstract: Aim The present study aimed to map and summarise the research on children, aged 0‐18 years, with Marfan syndrome, identify research gaps and point to research agendas. Methods A scoping review was systematically performed by searching multiple databases from January 1996 to April 2019. Primary studies presenting results on at least six individuals aged 0‐18 years with Marfan syndrome, diagnosed according to the Ghent nosology, were selected. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 91 publications
(696 reference statements)
1
13
0
1
Order By: Relevance
“…Compared to normative data, children and adolescents with HCTD and HCTD-subgroups MFS, LDS, EDS and hEDS reported increased fatigue, pain, disability and decreased general health, with most differences translating into very large-sized effects. These results match our previous qualitative studies on children and adolescents with MFS [9,10] reporting on limitations in activities and participation, and descriptive studies in children with MFS, EDS and hEDS reporting on fatigue, pain and the negative impact on daily (physical) functioning [7,[11][12][13][14][15][16][17]20]. Our results are also in line with studies using standardized validated measures in children with hEDS and HSD reporting on increased fatigue and pain [18], generalized hyperalgesia [21] and disability [17].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Compared to normative data, children and adolescents with HCTD and HCTD-subgroups MFS, LDS, EDS and hEDS reported increased fatigue, pain, disability and decreased general health, with most differences translating into very large-sized effects. These results match our previous qualitative studies on children and adolescents with MFS [9,10] reporting on limitations in activities and participation, and descriptive studies in children with MFS, EDS and hEDS reporting on fatigue, pain and the negative impact on daily (physical) functioning [7,[11][12][13][14][15][16][17]20]. Our results are also in line with studies using standardized validated measures in children with hEDS and HSD reporting on increased fatigue and pain [18], generalized hyperalgesia [21] and disability [17].…”
Section: Discussionsupporting
confidence: 91%
“…In previous qualitative semi-structured interview studies, parents of children with MFS (4-12 years) and adolescents with MFS (12-18 years) experienced problems of physical functioning, participation in activities and daily life and keeping up with peers [9,10]. Furthermore, studies in children with MFS and hEDS have reported fatigue and pain to negatively impact daily (physical) functioning [7,[11][12][13][14][15][16][17][18][19], a high incidence of pain-related disability [17] and deteriorating physical functioning over time [20]. To our best knowledge, no quantitative studies, using validated questionnaires, have been conducted into pain, fatigue and disability in children with MFS, LDS and molecularly confirmed types of EDS (hereafter EDS).…”
Section: Introductionmentioning
confidence: 99%
“…This also suggests that the Marfan phenotype tends to be more pronounced in patients with TVP. It is known that MFS has an impact on quality of life with a high risk for impaired quality of life 14,22 . The absences of cardiovascular manifestations or lower risk of onset and, in particular, interventions are essential for the quality of life experienced by patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that MFS has an impact on quality of life with a high risk for impaired quality of life. 14,22 The absences of cardiovascular manifestations or lower risk of onset and, in particular, interventions are essential for the quality of life experienced by patients. This could potentially have an impact on social performance, school or work performance and self-worth and well-being which is especially important in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Variants in the region of exons 24-32 are correlated with a severe form of MFS, called neonatal MFS [10,11]. Detailed information about the individual progress of the disease, with information about the involved organ systems and time of onset of symptoms depending on the specific FBN1 variant in other Marfan patients, is still lacking [12,13]. However, even though the Marfan genotype may not determine the whole progress of disease alone, information of the genotype effect on the phenotype outcome could improve individualized patient care with respect to the timing of follow-up visits, restriction of physical activity, medical treatment, and elective surgery, as a milestone for Marfan care.…”
Section: Introductionmentioning
confidence: 99%